Simple and rapid identification of saliva by detection of oral streptococci using direct polymerase chain reaction combined with an immunochromatographic strip. (March 2018) - Lee, Jee Won; Jung, Ju Yeon; Lim, Si-Keun
Highlights: A novel method for the identification of saliva in forensic samples was developed. The technique is based on the detection of oral bacteria by direct PCR and an ICS. Using this method, the entire analysis process was performed simply and rapidly. Oral bacteria were detected in most saliva swabs, but not in other body fluids. Oral bacteria were detected in a sufficient number of mock forensic samples. Abstract: In this paper, we describe the development of a novel method to detect oral bacteria by combining direct polymerase chain reaction (direct PCR) with an immunochromatographic strip (ICS), enabling the identification of saliva in forensic samples. Direct PCR was first used to directly amplify specific oral bacterial sequences (from Streptococcus sanguinis and Streptococcus salivarius ) from swab samples, circumventing the need for tedious sample preparation steps such as cell lysis and DNA extraction and purification. The resultant amplicons were then colorimetrically detected on an ICS, a much more convenient, cost-effective, and user-friendly detection method than those currently available, thereby allowing the presence or absence of the target oral bacteria to be determined with the naked eye. Moreover, the entire analysis process was performed rapidly and with ease using this combination of direct PCR amplification from swab samples and ICS-based amplicon detection. This method successfully detected S. sanguinis and S. salivarius in most of the saliva swab samples tested, and returned negative results using blood, semen, urine, and vaginal fluid swab samples. Furthermore, S. sanguinis and S. salivarius were detected in a large number of mock forensic samples using this technique, which suggests that direct PCR and ICS-based detection of oral bacteria is sufficient to demonstrate the presence of saliva. Thus, we believe that the proposed method could be very useful for the identification of saliva in forensic applications.